Prosthetic Memory and Tectonic Continuity in the Sustainable Refurbishment of Healthcare Heritage: The San Francisco Javier Psychogeriatric Centre in Pamplona - Yago Vaillo-Usón; Anton Aluja-Olesti (Buildings, 2026)
Sustainable refurbishment of historic healthcare complexes requires more than the preservation of isolated material fragments. It must reconcile cultural significance, continuity of care, inherited environmental qualities, contemporary technical requirements, material compatibility, and future adaptability. Taking the application of prosthetic memory as its central analytical and operative framework, this article examines the refurbishment and extension of psychiatric units U1.1 and U1.2 at the San Francisco Javier Psychogeriatric Centre in Pamplona, located within the former Manicomio Vasco Navarro. Through a qualitative case study, this research combines historical and project documentation, typological and construction analysis, and a diachronic comparison of the original complex, its pre-intervention condition, and the completed refurbishment. Five indicators (typological, environmental, tectonic, material compatibility, and temporal continuity) operationalise prosthetic memory as a strategy for sustainable heritage management. The results show that selective dismantling, functional extensions, reorganised circulation, reactivated courtyards and gardens, and pigmented architectural concrete restored the complex’s operational capacity while preserving the legibility of its inherited structure. This study proposes a transferable, value-based framework connecting cultural significance, functional viability, and sustainable refurbishment. It contributes to the protection of cultural heritage and to waste reduction through prevention, reuse, and recycling, while requiring adaptation to each cultural, climatic, regulatory, and healthcare context.